Soluble Neprilysin in the General Population: Clinical Determinants and Its Relationship to Cardiovascular Disease - Yogesh N. V. Reddy; Seethalakshmi R. Iyer; Christopher G. Scott; Richard J. Rodeheffer; Kent Bailey; Gregory Jenkins; Anthony Batzler; Margaret M. Redfield; John C. Burnett; Naveen L. Pereira (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background Neprilysin is a metalloprotease involved in proteolysis of numerous peptides, including natriuretic peptides, and is of prognostic and therapeutic importance in heart failure with reduced ejection fraction. No studies have investigated circulating neprilysin in the community, its clinical correlates, or its relationship to cardiovascular disease in the general population. Methods and Results Plasma neprilysin was measured in 1536 participants from Olmsted County, Minnesota, using a commercially available sandwich ELISA assay. Clinical and echocardiographic correlates and subsequent outcomes were determined. Soluble neprilysin is non‐normally distributed in the community (median: 3.9 ng/mL; interquartile range: 1.0–43.0 ng/mL). There was no relationship between plasma neprilysin and age (Spearman correlation: −0.04, P=0.16); body mass index (Spearman correlation: −0.04, P=0.16); glomerular filtration rate (Spearman correlation: −0.007, P=0.8); or A‐, B‐, or C‐type natriuretic peptides (Spearman correlation: 0.03, P=0.22; −0.001, P=0.96; 0.01, P=0.67, respectively). Among tertiles of neprilysin, the lowest tertile group had the highest prevalence of smokers (P<0.001), hypertension (P=0.04), dyslipidemia (P=0.03), and diastolic dysfunction (P=0.02). Soluble neprilysin was not prospectively associated with death or heart failure over a median of 10.7 years. Conclusions In a large community‐based cohort, for the first time, we described the distribution of circulating neprilysin in the general community. We observed that neprilysin does not correlate with natriuretic peptide levels and is not independently associated with adverse outcomes. The novel associations observed between low soluble neprilysin levels and an adverse cardiometabolic and smoking profile requires further investigation.